Mass spectrometry monitoring of drilling operations in water-doped lunar simulant under cryogenic conditions - Roberto Aguilar Ayala; Morgan A. Crabtree; Matthew L. Hancock; Alexander Jarnot; Janine E. Captain; Julie Kleinhenz; Erin Rezich; Kris Zacny; Vincent Vendiola; Zack Mank; Kenneth C. Wright; Jaime L. Winfield; et al. (Advances in Space Research, 2026)

Characterization of H2O vapor transport through lunar mare and lunar highland simulants at low pressures for in-situ resource utilization - Tyler P. Farr; Brant M. Jones; Thomas M. Orlando; Peter G. Loutzenhiser (Advances in Space Research, 2023)

Relating belowground microbial composition to the taxonomic, phylogenetic, and functional trait distributions of trees in a tropical forest - Albert Barberán; Krista L. McGuire; Jeffrey A. Wolf; F. Andrew Jones; Stuart Joseph Wright; Benjamin L. Turner; Adam Essene; Stephen P. Hubbell; Brant C. Faircloth; Noah Fierer (Ecology Letters, 2015)
The complexities of the relationships between plant and soil microbial communities remain unresolved. We determined the associations between plant aboveground and belowground (root) distributions and the communities of soil fungi and bacteria found across a diverse tropical forest plot. Soil microbial community composition was correlated with the taxonomic and phylogenetic structure of the aboveground plant assemblages even after controlling for differences in soil characteristics, but these relationships were stronger for fungi than for bacteria. In contrast to expectations, the species composition of roots in our soil core samples was a poor predictor of microbial community composition perhaps due to the patchy, ephemeral, and highly overlapping nature of fine root distributions. Our ability to predict soil microbial composition was not improved by incorporating information on plant functional traits suggesting that the most commonly measured plant traits are not particularly useful for predicting the plot‐level variability in belowground microbial communities.

The South American Monsoon System and the 1970s climate transition - Leila M. V. Carvalho; Charles Jones; Ana E. Silva; Brant Liebmann; Pedro L. Silva Dias (International Journal of Climatology, 2011)
The South American Monsoon System (SAMS) is characterised by intense convective activity and precipitation during austral summer. This study investigates changes in the onset, demise and duration of SAMS during 1948–2008. The results show a significant change in these characteristics in the early 1970s. Onset becomes steadily earlier from 1948 to early 1970s and has occurred earlier than 23–27 October after 1972–1973. Demise dates have remained later than 21–25 April after the mid‐to‐late 1970s. SAMS duration shows a statistical changepoint in the summer of 1971–1972 such that the mean duration was ∼170 days (1948–1972) and 195 days (1972–1982). Vertically integrated moisture flux is used to diagnose changes in mean state and reveal statistically significant increases over South America after 1971–1972. Copyright © 2010 Royal Meteorological Society

Moisture transport and intraseasonal variability in the South America monsoon system - Leila M. V. Carvalho; Ana E. Silva; Charles Jones; Brant Liebmann; Pedro L. Silva Dias; Humberto R. Rocha (Climate Dynamics, 2011)